Therapeutic actions of cyclosporine and anti-tumor necrosis factor alpha in collagen-induced arthritis and the effect of combination therapy. - Williams, R; Mauri, C; Mason, L; Marinova-Mutafchieva, L; Ross, SE; Feldmann, M; Maini, R (1998)
OBJECTIVE: To define the mechanisms of action of 2 novel drugs, cyclosporine and anti-tumor necrosis factor alpha (TNFalpha), in collagen-induced arthritis and to determine the effect of combination therapy. METHODS: Type II collagen-immunized DBA/1 mice with established arthritis were treated with cyclosporine alone, anti-TNFalpha alone, cyclosporine plus anti-TNFalpha, or saline. RESULTS: Cyclosporine was found to ameliorate arthritis, suppress interferon-gamma (IFNgamma) production by CD4+ T cells, and reduce TNFalpha expression in arthritic joints. However, cyclosporine did not directly inhibit TNFalpha production by macrophages, indicating that the decrease in TNFalpha expression observed in vivo was probably an indirect consequence of the reduction in type 1 T helper cell activity. Anti-TNFalpha also reduced IFNgamma production by T cells, indicating that TNFalpha is involved in the cellular immune response to collagen. Combined treatment with cyclosporine plus anti-TNFalpha had an additive therapeutic effect. CONCLUSION: Although cyclosporine and anti-TNFalpha target different points in the inflammatory pathway, there is an overlap in the consequences of their actions in vivo.